Inference and generalizability in applied linguistics : multiple perspectives / edited by Micheline Chalhoub-Deville, Carol A. Chapelle, Patricia Duff. - Chalhoub-Deville, Micheline; Chapelle, Carol A.; Duff, Patricia (J. Benjamins Pub. Co., 2006)
Concepts such as dependability/generalization and inferences are dealt with implicitly or explicitly in any research undertaken in applied linguistics. This volume provides a well-balanced and cross-disciplinary perspective on how researchers conceptualize inferences about learner acquisition and performances as well as dependability and generalizability of findings. The book is a collection of chapters by prominent researchers in applied linguistics, working in diverse domains such as vocabulary, syntax, discourse analysis, SLA, and language testing. The goal of the book is to bring attention.
Keywords: Applied linguistics -- Research.; Inference.; Reliability.